1999
DOI: 10.1046/j.1440-169x.1999.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell fate analysis of teloblasts in the Tubifex embryo by intracellular injection of HRP

Abstract: As in other clitellate annelids, embryonic development in the oligochaete Tubifex is characterized by the generation of five bilateral pairs of teloblasts (designated M, N, O, P and Q), which serve as embryonic stem cells to produce germ bands on either side of the embryo. A large part of the tissues comprising body segments has been assigned to the progenies of the teloblasts; however, the developmental fate of each teloblast has been inferred only from its initial position in the embryo. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 13 publications
(15 reference statements)
2
61
0
Order By: Relevance
“…Teloblasts very similar to the leech are found in non-leech clitellates (Tubifex for instance, Goto et al, 1999, Nakamoto et al, 2000. Non-leech clitellates however do not have a determinate number of segments and segments are sequentially added after embryogenesis during juvenile development and also during posterior regeneration.…”
Section: The Teloblasts Of Clitellatesmentioning
confidence: 99%
“…Teloblasts very similar to the leech are found in non-leech clitellates (Tubifex for instance, Goto et al, 1999, Nakamoto et al, 2000. Non-leech clitellates however do not have a determinate number of segments and segments are sequentially added after embryogenesis during juvenile development and also during posterior regeneration.…”
Section: The Teloblasts Of Clitellatesmentioning
confidence: 99%
“…A previous cell-lineage study has shown that PGCs, which are located in segments X and XI of stage 18 embryos, are derived from the mesodermal teloblast (M) lineage (Goto et al 1999a). …”
Section: Embryonic Origin Of Pgcsmentioning
confidence: 99%
“…This animal has testes and ovaries in body segments X and XI, respectively (Dixon 1915). It appears that PGCs are situated in these genital segments as early as the end of embryogenesis (Meyer 1929); it has been demonstrated that these cells are derived from the mesodermal teloblast lineage (Goto et al 1999a). The precise embryonic origin of the PGCs in T. tubifex remains to be determined, however.…”
Section: Introductionmentioning
confidence: 99%
“…The processes of Tubifex development have been described in previous studies (Shimizu 1982;Goto et al 1999a;Nakamoto et al 2000). Figure 1a summarizes the Tubifex developmental processes relevant to this study; we used this figure as a staging diagram.…”
Section: Comparison Of Temporal Expression Profilesmentioning
confidence: 69%
“…As a model lophotrochozoan animal, the oligochaete annelid Tubifex tubifex, a freshwater sludgeworm, has a body organization that is notable for its clear segmentation (Shimizu 1982;Goto et al 1999a;Nakamoto et al 2000). The ectodermal and mesodermal segmental structures arise from five bilateral pairs of coherent longitudinal columns (bandlets) of blast cells that are formed by five bilateral pairs of embryonic stem cells called teloblasts (named M, N, O, P, and Q).…”
Section: Introductionmentioning
confidence: 99%